Impact of Virtual Dissection Table (Anatomage) Versus Traditional Methods in Teaching Imaging and Radiology: A Comparative Study Among Respiratory Care Students in CAMSJ - Ebrahim, Doaa; Seedahmed, Hussam Mohammed; Al-Saud, Joud Mohammed Abu; Abbad, Zainb jameel Al; Al-Ghazwi, Safiah Jafar; Yatim, Zakaih Hussain; Alessa, Zahraa Ali (Journal of Posthumanism, 2026)
Imaging and radiology education is a core component of the Respiratory Care curriculum, as it supports students’ understanding of anatomical structures and the interpretation of diagnostic imaging modalities such as CT and MRI. Traditional teaching methods often depend on static, two-dimensional images from textbooks or clinical settings, which may limit students’ ability to visualize complex three-dimensional anatomical relationships and negatively affect knowledge retention and clinical application. Recent advances in educational technology have introduced tools such as the Anatomage Virtual Dissection Table, which provides interactive, three-dimensional visualization of real human anatomy derived from CT and MRI data. This study aims to assess the impact of integrating the Anatomage Virtual Dissection Table on Respiratory Care students’ learning, including short- and long-term memorization, academic performance, and learning preferences, in the Imaging and Radiology course at the College of Applied Medical Sciences, Jubail, Imam Abdulrahman bin Faisal University (IAU), Saudi Arabia. A comparative, questionnaire-based study was conducted among 46 second-year female Respiratory Care students with no prior experience in imaging and radiology. Participants were randomly assigned to either a traditional teaching group (n = 23) or a traditional teaching group integrated with the Anatomage Virtual Dissection Table (n = 23). A pretest was administered to assess baseline knowledge before instruction on segmental chest anatomy using CT images. Learning outcomes were evaluated immediately after the lecture and one week later to assess short- and long-term knowledge retention. Student perceptions and learning preferences were collected using a structured questionnaire. The statistical analysis of the study demonstrated a significant improvement in the academic performance of students who utilized the Anatomage Table compared to those taught through traditional methods. In the immediate post-test which assess the short-term retention of the students, the experimental group achieved substantially higher scores across all five evaluated domains, including chest anatomy and radiological interpretation. Furthermore, the long-term retention test confirmed that these students maintained a deeper understanding of the material over time, proving that the 3D interactive visualization effectively bridges the gap between theoretical knowledge and clinical imaging. In conclusion, the integration of the Anatomage Virtual Dissection Table serves as a transformative tool in respiratory care education. By providing a realistic and interactive learning environment, it significantly enhances both short-term comprehension and long-term memory retention. The study strongly recommends that educational institutions adopt a blended learning model that combines traditional lectures with advanced virtual technology. This approach not only improves student engagement but also ensures a higher level of competency in interpreting complex radiological data, which is essential for future clinical practice.